Peningkatan Hasil Belajar Tematik Tema 5 Cuaca melalui Penerapan Model Pembelajaran Kooperatif Tipe Talking Chip pada Siswa Kelas III SDN 3 Sukajawa Bandar Lampung - Karlina, Karlina (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
The purpose of this study is to improve teacher skills, student activities, and student learning outcomes. Describe the improvement of learning outcomes of third grade students of SDN 3 Sukajawa in thematic learning in Theme 5 Weather. This research design is a classroom action research which consists of 2 cycles in each cycle consisting of 2 meetings with the stages of planning, implementing the action, observing and reflecting. The research subjects were third grade students of SDN 3 Sukajawa. Data collection techniques used test and non-test techniques. Data analysis used quantitative descriptive analysis and qualitative descriptive analysis. Research results of this research is that by applying the cooperative learning model the talking chips type can improve the thematic learning outcomes of the 5 weather themes. suggestions for teachers of this method can be used by teachers in the learning process of other subjects.